Distribution and Activity of Ammonia-Oxidizers on the Size-Fractionated Particles in the Pearl River Estuary - Ma, Li; Tan, Shangjin; Liu, Hongbin; Kao, Shuh-Ji; Dai, Minhan; Yang, Jin-Yu Terence (Frontiers in Marine Science, 2021)
To distinguish between the distribution and activity of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in the Pearl River estuary (PRE), we investigated the DNA- and cDNA-based -amoA and arch-amoA genes on three size-fractionated particles of >3.0 μm, 0.45‒3.0 μm, and 0.22‒0.45 μm. Results showed that AOB were more abundant in the freshwater with high concentrations of ammonium (NH4+) and low dissolved oxygen, whereas AOA were dominant in the NH4+-depleted seawater and sensitive to temperature. Obvious shifts in ammonia-oxidizing communities were found along the salinity gradient in the PRE. AOB clearly presented a particle-associated nature, as evidenced by higher relative abundance of amoA genes attached to the large particles (> 3.0 μm) and their transcripts exclusively detected on this fraction. Moreover, higher transcriptional activity (indicated by the cDNA/DNA ratio) of AOB on the large particles, suggesting AOB were actively involved in ammonia oxidation despite their lower abundance in the mid- and lower estuarine regions. In contrast, AOA exhibited higher transcriptional activity on the 0.45‒3.0 µm and 0.22‒0.45 μm particles, implying the free-living strategy of these microbes. Together, these findings from field observations provide useful information on the ecological strategies of ammonia-oxidizing communities in response to different environmental conditions.